Refurbishing of personnel administration - India. Second Administrative Reforms Commission (New Delhi, 2008)
The roots of the civil service go back a long way in human history. The key to the survival of the ancient Egyptian civilisation that flourished as early as 3,000 BC, was the civil service - the historical model of all later bureaucracies
Keywords: Personnel administration